BIMBINGAN KEAGAMAAN DALAM MENINGKATKAN KECERDASAN SPIRITUAL REMAJA - Iswati Iswati; Noormawanti Noormawanti (Jurnal Bimbingan Penyuluhan Islam, 2019)
The development of Islam in its history was built with various kinds of problems that support the continuity of its teachings to convey to the people, and not a few often these problems are often also decorated with romantic challenges that must be passed in reaching the peak of its power. At the time of the Prophet Muhammad among the problems that existed was the existence of Arabian traditions at that time full of heresy, wrath and tyranny or better known as the era of jahilliyah, and many other munkar acts carried out by the Arabs in the era before da'wah Islam emerged. Reading the situation of the Arab nation so that this problem caused the Prophet Muhammad to begin his missionary journey by bringing the vision of '' liutammimamakarimulakhlak '' perfecting human morals especially at that time to glory, namely the formation of noble human behavior in order to realize a new civilization order well.the life of the Indonesian people, besides the word religion, also known as the word ad-din which comes from Arabic and the religious word from the European language. When viewed from the origin, "religion" actually comes from the Sanskrit words a and gam. A = no, and gam = leave. So, the word means "do not go away", "stay in place", "lasting", is inherited from generation to generation. Religion does have this nature. There are others who say that religion means the text or scripture, and religions do have scriptures